Aerobic granular sludge sequencing batch reactor performance under fluorinated pharmaceuticals shock loadings - Moreira, Irina S. (2015)
The widespread usage of pharmaceuticals is of increasing concern. Aerobic granular sludge sequencing batch reactors (AGS-SBR) constitute a promising technology for the treatment of wastewaters, however how the removal of carbon and nutrients can be affected by such micropollutants is largely unknown. This study evaluates the impact of different fluorinated drugs (ofloxacin, norfloxacin, ciprofloxacin and fluoxetine) on the performance of an AGS-SBR. During 468 days, a sequence of intermittent, alternating and/or continuous shock loads of pharmaceuticals were apllied to an AGS-SBR and the effects on the main biological processes were evaluated. Here we report on the effect of fluoroquinolones on reactor performnce. The organic removal, measured by COD, was not markedly affected by pharmaceuticals shock loads. Ammonium and nitrite were practically not detected in the bioreactor effluent indicating that the presence of the pharmaceuticals did not inhibit nitrification, whereas accumulation of nitrate in the effluent was observed, indicating that denitrification was affected. Phosphate removal was affected to some extent. There was no evidence of biodegradation whereas adsorption of the target pharmaceuticals to the AGS was observed, which were gradually released into the medium after withdrawal from the inlet stream.